Picoplankton Diel Variability and Estimated Growth Rates in Epipelagic and Mesopelagic Waters of the Central Red Sea - Al-Otaibi, Najwa; García, Francisca C.; Morán, Xosé Anxelu G. (Frontiers in Marine Science, 2021)
The diel variability of the abundance and cell size of picoplanktonic groups in the central Red Sea was monitored every 2 h in situ on 4 occasions (once per season) from 2015 to 2016. We distinguished Prochlorococcus, low (LF-Syn) and high (HF-Syn) fluorescence Synechococcus, small (Speuk) and large (Lpeuk) picoeukaryotes and two groups of heterotrophic prokaryotes of low (LNA) and high (HNA) nucleic acid content. The diel variability in abundance was less marked than in cell size and more apparent in autotrophs than heterotrophs. Specific growth rates were estimated by an empirical relationship from measurements obtained in bottle incubations of surface and deep samples collected in the winter compared with in situ variations in cell size over 24 h. Autotrophic picoplankton groups generally grew faster (0.23–0.77 d–1) than heterotrophic prokaryotes (0.12–0.50 d–1). Surface to 100 m depth-weighted specific growth rates displayed a clear seasonal pattern for Prochlorococcus, with maxima in winter (0.77 ± 0.07 d–1) and minima in fall (0.52 ± 0.07 d–1). The two groups of Synechococcus peaked in spring, with slightly higher growth rates of LF-Syn (0.57 ± 0.04 d–1) than HF-Syn (0.43 ± 0.04 d–1). Speuk and Lpeuk showed different seasonal patterns, with lower values of the former (0.27 ± 0.02 and 0.37 ± 0.04 d–1, respectively). HNA consistently outgrew LNA heterotrophic prokaryotes, with a higher growth in the epipelagic (0–200 m, 0.36 ± 0.03 d–1) than in the mesopelagic (200–700 m, 0.26 ± 0.03 d–1), while no differences were found for LNA cells (0.19 ± 0.03 d–1 and 0.17 ± 0.02 d–1, respectively). With all data pooled, the mean diel abundances of autotrophic picoplankton in the upper epipelagic and of HNA cells in the epipelagic and mesopelagic layers were significantly correlated with the specific growth rates estimated from cell size variations. Our high-resolution sampling dataset suggests that changes in growth rates underlie the noticeable seasonality of picoplankton recently described in these tropical waters.